2018
DOI: 10.1016/j.meegid.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bat-borne viruses and environment patterns

Abstract: Environmental modifications are leading to biodiversity changes, loss and habitat disturbance. This in turn increases contacts between wildlife and hence the risk of transmission and emergence of zoonotic diseases. We analyzed the environment and land use using remote spatial data around the sampling locations of bats positive for coronavirus (21 sites) and astrovirus (11 sites) collected in 43 sites. A clear association between viruses and hosts was observed. Viruses associated to synanthropic bat genera, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 31 publications
(49 reference statements)
0
44
0
5
Order By: Relevance
“…A largescale study conducted worldwide on 282 bat species from 12 families demonstrated the presence of coronaviruses on 8.6% of bats whereas the ratio was only 0.2% on non-bat species [36]. A relationship between viral richness and bat species richness was demonstrated, suggesting that the diversity of bat CoVs has been driven primarily by host ecology [36,41]. Preferred association between viral subclade and bat family was also observed.…”
Section: Intra and Interspecific Transmission Of Bat Virusesmentioning
confidence: 89%
See 2 more Smart Citations
“…A largescale study conducted worldwide on 282 bat species from 12 families demonstrated the presence of coronaviruses on 8.6% of bats whereas the ratio was only 0.2% on non-bat species [36]. A relationship between viral richness and bat species richness was demonstrated, suggesting that the diversity of bat CoVs has been driven primarily by host ecology [36,41]. Preferred association between viral subclade and bat family was also observed.…”
Section: Intra and Interspecific Transmission Of Bat Virusesmentioning
confidence: 89%
“…Even if the accumulation of knowledge through research works is probably influenced by these problems of perception of the risks, the example of coronavirus remains very interesting to tackle emergence phenomena. The increasing risk of pathogen transmission between bats, animals and humans in South East Asia is a consequence of the growing human population and of anthropization of environment (deforestation, agriculture) which have largely altered landscapes [41].…”
Section: Batsmentioning
confidence: 99%
See 1 more Smart Citation
“…South-East Asia host wide variety of bats and is habitat for 30% of the known global bat fauna. 38 Anthropogenic and environmental changes may impact the dynamic of virus transmission and public health. 38 India is facing rapid growth, economic development, speedy urbanization associated with massive deforestation, overcrowding of cities, movement of migrant workers.…”
Section: Possible Causes Of Re-emergence Of Nipah Virus In Indiamentioning
confidence: 99%
“…38 Anthropogenic and environmental changes may impact the dynamic of virus transmission and public health. 38 India is facing rapid growth, economic development, speedy urbanization associated with massive deforestation, overcrowding of cities, movement of migrant workers. Political instability is associated with decrease in nations output, Economic crisis, currency devaluation, and inflation leading to decrease in funding for health care infrastructure.…”
Section: Possible Causes Of Re-emergence Of Nipah Virus In Indiamentioning
confidence: 99%